Self-powered, on-demand transdermal drug delivery system driven by triboelectric nanogenerator. (August 2019) - Ouyang, Qingling; Feng, Xueling; Kuang, Shuangyang; Panwar, Nishtha; Song, Peiyi; Yang, Chengbin; Yang, Guang; Hemu, Xinya; Zhang, Gong; Yoon, Ho Sup; Tam, James P.; Liedberg, Bo; et al.
Abstract: In this work, we present a self-powered and on-demand transdermal drug delivery system driven by triboelectric nanogenerator (TENG). A miniaturized TENG and a home-built power management circuit were designed to trigger the electric-responsive drug carrier for controlled drug release, as well as to activate the iontophoresis treatment for enhanced drug delivery efficiency. In the system, the TENG can harvest electricity from bio-mechanical energy, and the power management circuit is able to store, adjust, and stabilize the electricity for on-demand drug release actions. Our results demonstrate that the on-demand drug release can be simply realized by operating the TENG. Manually rotating the TENG (30–40 rpm) for 1.5 min can release a drug dosage of 3 μg/cm 2 . Furthermore, the system has achieved tunable drug release rate for the transdermal drug delivery: the rate can be tuned from 0.05 to 0.25 μg/cm 2 per minute by changing the duration of TENG charging or the resistance of the power management circuit. In addition, ex vivo experiments on porcine skin validate the performance of such TENG-based drug delivery system with ∼50% enhancement over conventional transdermal patches. The proposed system is intended to provide patients with an easy approach to achieve customized rate and dosage of drug release. Graphical abstract: Image 1 Highlights: We present a portable TENG-based transdermal drug delivery system for precise and on-demand drug dosing. Our device is based on TENG operation and exhibits tunable drug release rate: 0.05 to 0.25 μg/cm 2 per minute. Two methods for controlling the drug release rate are demonstrated to satisfy customized needs of personalized healthcare. Upon hand rotation of TENG for 1.5 min, 3 μg/cm 2 of drug release is recorded from the electric-stimulated drug carriers. The proposed system demonstrates a non-invasive method for drug delivery with enhanced efficiency ( 50 %) in the dermis.